PARP inhibition in prostate cancer - Nientiedt, Cathleen; Duensing, Anette; Zschäbitz, Stefanie; Jäger, Dirk; Hohenfellner, Markus; Stenzinger, Albrecht; Duensing, Stefan (Genes, chromosomes & cancer, 2021)
Defects in DNA damage repair genes are more common in prostate cancer than previously thought. These alterations provide an opportunity for precision oncology approaches and a number of studies have now shown that PARP inhibitors can have significant antitumor activity in men with DNA damage repair-deficient metastatic castration-resistant prostate cancer. This review summarizes the key clinical trials related to the use of PARP inhibitors in prostate cancer. Besides clinical outcomes, toxicity, and PARP inhibitor resistance, the role of different DNA repair genes in the response to PARP inhibition will be discussed.